Integrating Lombok’s Local and Islamic Literature into Bilingual Digital Storytelling for Culturally Responsive Learning Materials - Anisa Nur’aini; Sukardi Sukardi; Nurul Wahidah (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study examines the early-stage adaptation of Lombok’s local and Islamic literature into bilingual digital storytelling materials to strengthen children’s literacy. Responding to the persistent gap between students’ cultural backgrounds and the limited availability of engaging digital reading resources, this research aims to identify culturally grounded narratives and to design an initial model of a bilingual storytelling application. Employing a qualitative descriptive design within the ADDIE (Analysis–Design) framework, data were collected over three months from six English teachers, thirty students from elementary and Islamic schools, and twelve cultural informants, including storytellers, religious figures, and librarians. The data were obtained through interviews, participatory observations, and documentation of oral and written traditions. A total of fourteen literary works, including Princess of Mandalika, Cupak Gerantang, Tegodek Godek, The Legend of Masbagik, as well as stories of Prophet Ibrahim and Prophet Yusuf, were analyzed and adapted into simplified bilingual scripts. Thematic analysis was employed to examine narrative content and pedagogical relevance, while data validity was ensured through source triangulation, method triangulation, and expert validation involving literacy specialists and local cultural guardians. The findings reveal strong enthusiasm among students toward culturally familiar stories, with approximately seventy percent demonstrating improved comprehension indicators, vocabulary recall, and engagement during bilingual reading sessions. Teachers also reported increased participation and motivation when digital and visual elements were introduced. The study concludes that integrating local and Islamic literature into bilingual digital storytelling offers a culturally sustaining pathway for curriculum development, supporting literacy development, character education, and cultural identity reinforcement through contextually relevant digital media.